Investigating domain analysis in language choice and language shift of the Banjarese And Cocos Malay Speech Communities in Malaysia. - Che Lah, Salasiah (Universiti Sains Malaysia, 2017)
The resurgence of interest in and research into language maintenance and shift in recent years marks the realization that the world is rich in cultures and languages that need to be preserved (Garcia, 2003). Language shift refers to change by a speaker, a group of speakers, and/or a speech community from the dominant use of one language in almost all spheres of life to the dominant use of another language in almost all spheres of life.